Direct Vasocontractile Activities of Bupivacaine Enantiomers on the Isolated Rat Thoracic Aorta - Mai Mukozawa; Ko Takakura; Maki Mizogami (Anesthesiology Research and Practice)
Background. In vitro studies with isolated arteries have shown direct vasoactivity of racemic bupivacaine. However, there is little information on the direct vasoactivities of bupivacaine enantiomers, S(−)- and R(+)-bupivacaine. Methods. We performed functional examinations using isolated intact thoracic aortic rings from male Wistar rats. Changes in ring tension produced by S(−)-, R(+)-, or racemic bupivacaine were measured in Krebs solution. Results. S(−)-bupivacaine produced the strongest contraction of the three agents. R(+)-bupivacaine showed limited vasoconstriction. The effects of racemic bupivacaine were located between these two. Conclusion. Each bupivacaine enantiomer showed specific vasocontractile activity, which affects the activity of racemic bupivacaine.